Resources integrators in social media : an analysis of value cocreation (2024)
Purpose This study aims to identify the groups of value cocreators in the context of social media in the retail banking industry and resources that predict customer membership among different groups of value cocreators. Design/methodology/approach This study reviewed the literature and developed measurement instruments for the constructs of interest. Data were collected from 406 customers in an emerging market in 2019 and analyzed using latent profile analysis. Findings This study identified three profiles of value cocreators on social media based on the actual practices of resource integration that enliven value cocreation. Second, this study explains the differences in the performance of resource integration practices to cocreate by the types of resources that customers integrate into social media. Third, this study fills the need for knowledge of value cocreation in different contexts and industries (e.g. banks). Originality/value This study analytically relates a set of resources to the variety and intensity of the value cocreation practices adopted by bank customers in interactive environments. The emphasis on how value cocreation practices in online environments combined with customer resources (e.g., a person-centered approach) allows to identify unique profiles of value cocreators on social media. The findings inform managers of the profiles of cocreators, which customers are more attractive as value cocreators on social media, and which resources managers should help customers develop to increase cocreation on social media.